ANALISIS KEUNTUNGAN PETERNAK SAPI PERANAKAN ONGOLE (PO) YANG MENGGUNAKAN INSEMINASI BUATAN (IB) DI KECAMATAN TOMPASO BARAT - Monintja, Mario Y; Oley, F. S.; Sondakh, B F; Oroh, F. N.S (Universitas Sam Ratulangi, 2015)
ABSTRACT Ongole cross bread has important role in the economical needs of people in Tompaso Barat. In addition as beef cattle, household farmers also use it as a working cattle, source of fertilize and investment. In addition to farmer’s income and the acceleration growth of cattle population, in the year of 2011, District West Tompaso Barat did an artificial insemination program. The problem was whether this program is beneficial for the farmer or not. The aim at this research is to analyze the profit of farmers using artificial insemination program. This research was conducted using survey method involving about 169 farmers raising Ongole crossbred cattle at West Tompaso District applying artificial insemination. The data were analyzed by profit analysis. Result showed that the total income received from the total sale of the beef cattle using artificial insemination were IDR 490,950,000.- with the total cost of IDR 468,945,750. The profit of the household farmers was the balance between the total income and the total cost getting IDR 21,504,250. The average income of the respondent was about IDR 716,808. Therefore, it can be concluded that the household farmers raising Ongole crossbred cattle get more profit when they used artificial insemination. Based on this research it can be suggested that the beef cattle management should be maintained on the bases of agribusiness. Keywords: Profit, Ongole crossbred cattle, Artificial Insemination